2020
DOI: 10.1016/j.jclepro.2020.121922
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nutrient management on soil organic carbon storage, crop production, and yield stability varies under different climates

Abstract: Our understanding on how soil organic carbon (SOC) storage, crop yield, and yield stability are influenced by climate is limited. To critically examine this, the impact of long-term (≥10 years) application of nutrient management practices on SOC storage, crop productivity, and yield stability were evaluated under different climatic conditions in China using a meta-analysis approach. The cropping area of China was divided into four distinct groups based on local climatic conditions (warm dry, DW; warm moist, WM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…Furthermore, we noticed that the MNPK compared with M and NPK enhanced the wheat grain yield by 55.67% and 24.14%, maize grain yield by 76.65% and 33.63%, and soybean grain yield by 23.42% and 18.79%, respectively (Figure 2a). Earlier studies also supported our results and reported that mixed application of manure and mineral fertilization increased grain yields compared with mineral only treatments and implied this yield increment to better nutrient uptake (Gai et al, 2018;Waqas, Li, Smith, et al, 2020;Wei et al, 2016).…”
Section: Association Among Soc and Tn Stocks Depth Increment And Crop...supporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we noticed that the MNPK compared with M and NPK enhanced the wheat grain yield by 55.67% and 24.14%, maize grain yield by 76.65% and 33.63%, and soybean grain yield by 23.42% and 18.79%, respectively (Figure 2a). Earlier studies also supported our results and reported that mixed application of manure and mineral fertilization increased grain yields compared with mineral only treatments and implied this yield increment to better nutrient uptake (Gai et al, 2018;Waqas, Li, Smith, et al, 2020;Wei et al, 2016).…”
Section: Association Among Soc and Tn Stocks Depth Increment And Crop...supporting
confidence: 91%
“…The positive role of manure application alone and in combination with mineral fertilizers in improving soil health dynamics and crop productivity has been described in the past on both regional and national croplands. For example, in Chinese croplands, the average SOC sequestration of 0.43 Mg C ha −1 per year can be achieved through the integrated use of manure and mineral fertilizers, and each increase of 1 Mg C ha −1 leads to an increase in grain yields of rice, wheat, and maize by 143, 255, and 202 kg ha −1 , respectively (Waqas, Li, Smith, et al, 2020). Likewise in a long‐term study, Kätterer et al (2011) observed an incremental trend in SOC stock with the application of manure while Zhengchao et al (2013) found that long‐term manure fertilization may result in no change or even a net loss of C and N stocks.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that crop yields increase with increased fertilization [19,36,37]. Our results likewise showed that bamboo-shoot yield increased with increasing fertilizer application (Figure 1), which was due to the increases in soil nutrients (Olsen P, AN, SOM, and AK) contents via applying NPK inorganic compound fertilizers (Tables A1 and A2).…”
Section: The Bamboo-shoot Yieldsupporting
confidence: 77%
“…Over the past few decades, intensive farming practices, e.g., excessive inorganic fertilization and tillage, have been widely adopted to enhance crop productivity to meet the increasing domestic food demand in China. These practices degrade soil quality, meaning more unfavorable soil conditions for crops to grow (Droste et al, 2020;Waqas et al, 2020). Degraded soil quality will also make a cropping system more vulnerable to warming according to our results.…”
Section: Discussionmentioning
confidence: 56%